Perbandingan Sikap Empati Mahasiswa Sebagai Calon Konselor Berdasarkan Analisis Gender - Hasan Bastomi (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2020)
This study aims to compare the empathy attitudes of Islamic Education Guidance and Counseling students at the Kudus State Islamic Institute as prospective counselors based on gender analysis. This study used a qualitative method with the type of Field Research research with a sample size of 120 Islamic Education Guidance and Counseling students at the Kudus State Islamic Institute, extracting data using questionnaires, observations, interviews and documentation and then analyzed using a descriptive percentage table. The results of this study indicate that there are differences in empathy between female research participants and male research participants with affective empathy components in the good category, namely 32% versus 42% and cognitive empathy in the good category 79% versus 80%. This can happen due to various things. Initially, the stereotype said that women are more nurturance and have an interpersonal orientation compared to men so that it has an impact on the level of empathy they have.